Mediating Effect of Organizational Commitment between Job Security and Employee Knowledge Sharing Behavior in the Telecommunication Sector of Bangladesh - Nishat, Sabrina Sharmin; Haque, Md. Anamul; Tazin, Farzana (Advances in Social Sciences Research Journal, 2022)
The main purpose of the study is to determine how the Bangladeshi telecommunications sector can sustainably exercise its employees’ knowledge sharing behavior in order to gain a competitive edge in the local and global marketplace through the mediating effect of organizational commitment between knowledge sharing behavior and job security. Data for this study has been collected using a questionnaire survey from 189 participants of which 162 were found to be fit for further analysis adapting the Partial Least Square method. Results of the study showed significant effect of employee perception of job security on their knowledge sharing behavior. Once more, job security showed a strong positive correlation with organizational commitment. For organizational commitment, knowledge sharing behavior were also found to be increased. To conclude, the mediating relation was also found to be significant in this study. Thus, it might be suggested that management of these telecommunication organizations require to be more considerate about increasing on employee knowledge sharing behavior in terms of knowledge collecting and knowledge donating which may help them to attain sustainable competitive advantage in the industry. Therefore, it is essential for the organization to ensure employee continuity in the workplace which may minimize their depression to contribute more.